Transcriptional analyses of interferon-inducible mRNAs. - Kusari, J (1987)
Using nuclear runoff transcription assays we demonstrated that alpha interferon-mediated induction of transcription of four mRNAs in HeLa monolayer cells needed ongoing protein synthesis and that such a need could be obviated by pretreating the cells with gamma interferon which, by itself, did not induce transcription of these mRNAs. In another human cell line, RD-114, synthesis of alpha interferon-inducible mRNA 561 did not need ongoing protein synthesis. In this line, however, in which interferon inhibits replication of some viruses but not of others, transcription of two of the six interferon-inducible mRNAs that we examined was not appreciably enhanced by interferon.